Life after Bali: Renewing the world trade negotiating agenda - Suparna Karmakar (Bruegel, 2013)
The crisis has contributed to a slowdown in global trade volumes, with trade virtually stagnant in the twelve months to July 2013. In this context, fruitful negotiations in the World Trade Organisation's 9th Ministerial Conference in Bali are crucial to sustain the institution's credibility and prove that multilateral negotiations can still deliver success. WTO trade talks are the only ongoing trade liberalisation process that has development at its core. The Doha mini-package under consideration at Bali is a collection of watered-down but deliverable elements of a deal comprising agriculture, trade facilitation and special and differential treatment/less developed country concessions. Post-Bali, the WTO should aim to reverse the current disenchantment with multilateral trade negotiations. This means formulating a relevant trade negotiating agenda with an understanding of global value chains at its core. However, the transition to the new agenda requires a closure of the ongoing Round. The easiest way to conclude the Doha Round would be to select another discrete set of deliverables that fulfills the development commitment of the Doha Development Agenda, thus paving the way for a new Round.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Internationale Handelspolitik; Handelsliberalisierung; WTO-Verhandlungen